When should children with HIV infection be started on antiretroviral therapy? - Steven B Welch; Di Gibb (PLoS Medicine)
Background to the debate The advent of highly active antiretroviral therapy (HAART) dramatically improved the prognosis for both adults and children infected with HIV who had access to treatment. However, the optimal timing for initiating treatment remains controversial, particularly in children. This debate lays out the case for deferred treatment against the case for early initiation of HAART in children.